Characterisation of one-dimensional CdS nanorods synthesised by solvothermal method - Anukorn Phuruangrat (2018)
One-dimensional (1D) cadmium sulfide nanorods were successfully synthesised using cadmium nitrate and sulfur powder as starting materials and polyvinyl alcohol (PVA, MW = 1 25,000) as a capping agent in ethylenediamine as a solvent by solvothermal method at 200°C for 24 and 72 h. X-ray diffraction patterns (XRD) indicated a single phase of hexagonal wurtzite CdS structure, of which the results are in accordance with those of selected area electron diffraction (SAED). The morphologies of CdS were observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) which showed 1D nanorods. The length and diameter of CdS nanorods were increased when PVA was added and the reaction times were prolonged. High resolution transmission electron microscopy (HRTEM) showed that growth direction of wurtzite CdS nanorods is along [001] direction or c-axis. Raman spectra presented the 1LO and 2LO at 299.36 and 600.72 cm-1, respectively. The 2LO/1LO intensity ratios were increased when the length of CdS nanorods became longer.